Design of Dual-Passband Microstrip Filtering Antenna Using Dual-Mode Closed Loop Resonators and Defected Ground Structure - Alkhafaji, Mohammed K.; Al-Momin, Mohammed (Iraqi Journal for Electrical and Electronic Engineering, 2024)
This paper presents a new microstrip dual-mode closed-loop resonator (DMCLR) that is used to design lower insertion loss and better transmission dual-passband filtering antenna. The dual passband center frequencies of the presented filtering antenna are located at foI=5.52 GHz and foII= 6.65 GHz. The presented dual-mode, dual-passband microstrip filtering antenna results are simulated and optimized by using Computer Simulation Technology (CST) software and defected ground structure technique. Three modes of dual-mode resonators have been utilized to design the dual- passband microstrip filtering antenna and compare their results. The presented dual-mode, dual-passband microstrip filtering antenna is established on FR-4 epoxy dielectric material which has a relative permittivity εr= 4.3 which has height thickness h = 1.6 mm and loss tangent tan δ=0.002. Defected Ground Structure (DGS) technique has been utilized to improve the performance of the presented dual-mode, dual-passband microstrip filtering antenna.